2018
DOI: 10.5304/jafscd.2018.081.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Barriers to SNAP/EBT Acceptance in Farmers Markets: A Survey of Farmers

Abstract: Farmers play a critical role in increasing access to and affordability of fruits and vegetables in lowincome communities by accepting Supplemental Nutrition Assistance Program (SNAP) benefits at farmers markets. However, only 40% of farmers markets nationally accept SNAP benefits. This study evaluates barriers farmers perceive in accepting SNAP in farmers markets. We recruited 134 farmers using convenience sampling from six pre-season regional growers meetings hosted in Alabama; 92 farmers met inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Farms, are seeking to respond to food insecurity is through joining the growing number of farmers markets accepting SNAP benefits. However, even when markets successfully navigate the cumbersome process of obtaining the necessary approval and technology for SNAP, high costs, lack of transportation, and an overrepresentation of whiteness in the cultural organization of market spaces remain barriers for low-income and marginalized customers (Alkon & McCullen, 2010;Hoover, 2013;Kellegrew et al, 2018;Larimore, 2018). The amount of funding spent at farmers markets through SNAP remains a very small portion of overall expenditures (Farmers Market Coalition, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Farms, are seeking to respond to food insecurity is through joining the growing number of farmers markets accepting SNAP benefits. However, even when markets successfully navigate the cumbersome process of obtaining the necessary approval and technology for SNAP, high costs, lack of transportation, and an overrepresentation of whiteness in the cultural organization of market spaces remain barriers for low-income and marginalized customers (Alkon & McCullen, 2010;Hoover, 2013;Kellegrew et al, 2018;Larimore, 2018). The amount of funding spent at farmers markets through SNAP remains a very small portion of overall expenditures (Farmers Market Coalition, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to prior research that found barriers to using farmers’ markets in rural settings. 41 Higher rates of SNAP use at the farmers’ markets located in rural areas may be due to the fact that there is higher farmers’ market density in metropolitan areas, which provides greater choice to SNAP consumers but distributes the consumer base among multiple markets. This may result in lower rates of SNAP use at some of the markets in metropolitan areas.…”
Section: Discussionmentioning
confidence: 99%
“…Food stamps and supplemental nutrition assistance programs (SNAP) are publicly funded and administered responses to food-related issues; however, not all individuals who face food insecurity qualify for or utilize these programs (Daponte 2000). Food stamps and SNAP can also restrict food choices including choices to eat fresher and healthier foods (Guthrie et al 2007;Hunt 2018) or local foods (Kellegrew et al 2018). Relatedly, most U.S. farmers markets (~60%) do not accept SNAP and/or EBT benefits (Kellegrew et al 2018).…”
Section: Food Insecurity and Waste Solutionsmentioning
confidence: 99%
“…Food stamps and SNAP can also restrict food choices including choices to eat fresher and healthier foods (Guthrie et al 2007;Hunt 2018) or local foods (Kellegrew et al 2018). Relatedly, most U.S. farmers markets (~60%) do not accept SNAP and/or EBT benefits (Kellegrew et al 2018). Community responses to help individuals in need can include community gardens, community kitchens, co-ops, food banks, food cupboards, food drives, food pantries, and gleaning programs (Brashers et al 2002;Carney et al 2012;Daponte 2000;Riches 2002;Tarasuk and Eakin 2005;Tarasuk and Reynolds 1999).…”
Section: Food Insecurity and Waste Solutionsmentioning
confidence: 99%